AUTOMATIC WATER MONITORING AND DOSING SYSTEM FROM A BASIN (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
Liquid measurement, dosing, and control systems are based on applications dedicated to measuring the amount of liquid, controlled filling of enclosures, and disinfection of liquids and surfaces. The applications of such a system are multiple, from maintaining the quality of drinking water to the maintenance of swimming pools, and can be extended to the food and pharmaceutical industries. This paper presents an experimental setup for monitoring and controlling water in a liquid tank. The system is ordered with the help of development boards and has a didactic purpose, the paper presents the process of choosing the components and how to develop the application. The particular case of the presented model is developed for monitoring the water in a pool.
Keywords: AUTOMATIC SYSTEM; MONITORING AND DOZING; WATER; POOL